Скляренко В. Г. Історія українського наголосу : Іменник - Карпенко, Ю. (Мовознавство, 2009)
Рецензія на книгу: Скляренко В. Г. Історія українського наголосу : Іменник. К. : Наук, думка, 2006. — 709 с.